IMPACT OF CONVERTING AGRICULTURAL LAND INTO AN OIL AND GAS MINING AREA IN GAYAM DISTRICT, BOJONEGORO REGENCY - Tria Mei Hidayati; Hamidah Hendrarini; Dona Wahyuning Laily (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Bojonegoro Regency has the nickname "Food and Energy Granary", is one of the districts that participates in oil and gas exploitation projects, especially those managed by PT Exxon Mobile Cepu Limited (EMCL). The discovery of oil sources in Gayam District resulted in the conversion of agricultural land into the oil and gas industry. The majority of the people earn their living as farmers with a low average education level. The existence of the oil and gas industry causes agricultural land to experience significant decline and this has a changing impact on the social and economic life of the community around the location. This research aims to analyze the factors that influence the conversion of agricultural land and analyze the socio-economic impact of carrying out land conversion activities for the people of Gayam District. This research uses multiple linear regression methods to analyze influencing factors and descriptive qualitative methods are used to analyze the impact of land conversion. The results of this research show that the factors that influence land conversion are policy factors, land coverage, land area and farming experience. Meanwhile, factors that do not influence are education, farmer's age, number of family dependents and crop harvest age. The social impact felt by society is the emergence of inequality in social strata and a shift in the workforce, where the farming profession is decreasing. Viewed from an economic perspective, it shows that the cost of living is increasing, although some people have experienced a decrease in income, but quite a few people have seen their income increase. Existing policies need to be further improved to protect the welfare of local farmers.